Applied Neural Networks and Soft Computing - Zgallai, Walid A., contributor; Chen, Jeng-Fung, contributor; Do, Quang Hung, contributor; Hsieh, Ho-Nien, contributor; Huang, Xiang, contributor; Wang, Zhizhong, contributor; Lee, Dongoun, contributor; Kim, Seungho, contributor; Kim, Sangyong, contributor; Meng, Changqing, contributor; Zhou, Jianzhong, contributor; Tayyab, Muhammad, contributor; et al. (United Kingdom, UK : Koros Press Limited, 2017)
Includes bibliographical references and index